Acute Pancreatitis as a Complication of Choledochal Cyst - Hendra Koncoro; I Dewa Nyoman Wibawa (The Indonesian Society for Digestive Endoscopy, 2012)
Choledochal cysts (CCs) are rare congenital disorders of the biliary tree which are associated with biliary tract and pancreatic complications. Its etiology is still unknown, but some evidences suggest that CCs are caused by infection during embryogenesis. The laboratory evaluation reveals abnormalities due to pancreatobiliary complications, such as ascending cholangitis, cholecystitis, and pancreatitis. Radiologic examination may delineate the structural abnormalities occured in CCs and confirm the diagnosis. The major mortality is caused by cholangiocarcinoma. This case discussed the diagnosis and treatment of a 20-year-old male with choledochal cyst and its complications. Management consists of therapy on complication and definitive therapy. Keywords: choledochal cyst, acute pancreatitis, cholecystitis